Investigating the Effects of Various Root Canal Irrigation Solutions on Tissue Dissolution and Microbial Control - Ashima Jakhar; Anjali Shrivastava Vats; Simarjeev Singh; Gagandeep Thind; Nausheen Aga; Muhammad Atif Saleem Agwan; Ramanpal Singh Makkad (Wolters Kluwer Medknow Publications, 2024)
Background: Both the mechanical cleansing effect and the irrigants' capacity to disintegrate tissue are necessary for irrigation to be successful. Strong antibacterial but not poisonous to the periapical tissues and increased pulp tissue dissolution irrigant are all desirable qualities in an irrigant. Aim: To assess and compare the antibacterial properties and pulp tissue dissolving activity of various irrigation solutions. Methods and Materials: A total of 240 human mandibular permanent premolar teeth that were extracted recently for periodontal or orthodontic reasons were used in this investigation. Following irrigation, blood agar plates were used to conduct colony-forming unit (CFU) counts of the microorganism breeding colonies. Next, log CFU was computed. Before evaluating the ability of the five distinct irrigants utilized in this investigation to dissolve the frozen pulp tissues, the tissues were first smashed into smaller pieces using a mallet. Results: The bacterial count after irrigation in category 1 (normal saline), category 2 (aqueous ozone), category 3 (ethylenediaminetetraacetic acid (EDTA)), category 4 (chlorhexidine gluconate (CHX)), category 5 (super-oxidized water), and category 6 (sodium hypochlorite (NaOCl)) was 6.08 ± 0.87 log CFU mL-1, 0.92 ± 0.89 log CFU mL-1, 4.15 ± 0.20 log CFU mL-1, 3.34 ± 0.46 log CFU mL-1, 0.21 ± 0.52 log CFU mL-1, and 0.00 ± 0.00 log CFU mL-1, respectively. Conclusion: NaOCl has maximum antimicrobial reduction and pulp tissue dissolution property.